Variasi Konsentrasi Sari Jeruk Nipis sebagai Disinfekatn Kuman Udara di Ruang Perawatan Rumah Sakit PKU Muhammadiyah Yogyakarta - Rafita Estu Wulandari; Y.B. Kamat Kartono; Muryoto Muryoto (Poltekkes Kemenkes Yogyakarta, 2013)
The air quality in caring rooms of hospitals is one of important things that have to be considered regarding to the prevention of nosocomial infection. The examination results of air bacterial number in the caring room of PKU Muhammadiyah Hospital of Bantul in 11 February 2013, still exceeded the maximum threshold permitted by the regulation, i.e. 200-500 CFU/m3. One of the alternatives for controlling the condition is by using lime juice concentration as disinfectant, because the fruits contain flavonoid, an anti-inflammatory, anti bacterial, and anti-fungal substance; citric acid, as cleansing agent; and has acidity which suitable for bacterial controlling. The purpose of the study was to determine the influence of five concentration variations of lime juice in decreasing air bacterial number in the caring rooms of the hospital, by conducting a true experiment which employed one group pre-test post-test only design. The sample of air bacteria were obtained before and after the fogging process by using air pump sampler and midget impinger. The results showed that the highest the concentration of lime juice, the highest the bacteria number will be reduced. The average reduction of air bacterial number for lime juice concentrations of 20%, 40%, 60%, 80% and 100% were measured 11,51%; 13,84%; 22,70%; 45,26%;and 55,20%, respectively. One way anova test acquired p-value less than 0,001, which can becloncluded that the difference of the reduction for each concentration were statistically significant. The subsequent LSD test confirmed the evidence that 100% concentration gave the highest results. However, since the yielded bacterial number was still exceeding the permitted limit, it is advised that in its application, the fogging of 100% lime juice concentration should be carried out in five consecutive replications.